Faktor-Faktor Yang Memengaruhi Cash Holding - Adrian Nathan Heryanto, Sofia Prima Dewi (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
This study aims to obtain empirical evidence regarding the determinants of cash holding of manufacturing companies listed on the Indonesian Stock Exchange during 2017-2019 period with a sample of 38 companies after going through the method. purposive sampling. Data processing uses multiple regression analysis helped by Eviews 10 and Microsoft Excel 2010. The results show that leverage has a significant negative effect on cash holding, while profitability, firm size, managerial ownership, and capital expenditure have no significant effect on cash holding. The implication of this research is the importance of cash holding for company as a source of funding and as a flexible asset to financing an investment.